SEJARAH PERKEMBANGAN PENDIDIKAN ISLAM DI SUMATERA (Suatu Kajian terhadap Tokoh dan Lembaganya) - Siti Aisyah Abbas; Nur Rahma Asnawi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
Islam entered Minangkabau between the 12th and 13th centuries AD, through two channels namely; pathway from Aceh and pathway from Malacca. Islam was introduced by the preachers and Arab merchants who settled in eastern Minangkabau, especially in the watershed that led to the center of the Minangkabau kingdom in the interior. The expansion of Samudra Pasai kingdom to eastern Minangkabau was very influential for the intensive spread of Islam in this region and other Minangkabau regions. The Islamization process took place peacefully, because it was introduced through local wisdom approaches to the community in the local cultural environment. In addition, the initial approach undertaken by the preachers in a persuasive and acculturative way to the customary laws adopted by the community, further facilitated the process of Islamization where they are, even as the beginning of a fusion between Islam and Minangkabau custom has given rise to a consensus that reads